A Case of Granulomatosis with Polyangiitis with Various Breast Lesions as the Initial Symptoms: A Case-Based Review - Masatoshi Kawataka; Toshiki Kido; Reina Tsuda; Takafumi Onose; Ryoko Asano; Miho Yamazaki; Naonori Sugishita; Hiroyuki Hounoki; Toshiko Kakiuchi; Koichiro Shinoda; Kazuyuki Tobe (Case Reports in Rheumatology)
A 44-year-old woman presenting with pus-like discharge from the nipples visited our hospital for scleritis. Subcutaneous induration and ulceration were found on her breast. She was diagnosed with granulomatosis with polyangiitis (GPA) considering scleritis, sinusitis, cutaneous granuloma formation, and antiproteinase 3-antineutrophil cytoplasmic antibodies and was successfully treated with glucocorticoids. Fifteen months later, she developed pulmonary consolidation and a right breast nodule. Biopsies of the breast nodule showed granulomatous vasculitis, and she was treated with rituximab. While breast involvement in GPA is rare, unilateral breast mass is a typical clinical feature; thus, GPA should be considered in such cases.